The Uses of Cultural Heritage of Port Cities in Post-Industrial Societies, c.1980-2020 - Yang, Zhen (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2022)
Cultural Heritage of Port Cities (CHPC) is a symbol and reflection of how people interact with the sea. It comprises both material (e.g. docklands, landscapes) and immaterial aspects (e.g. lifestyle and activities of local communities); therefore is the fluid mix of elements that constantly changes according to its users. This thesis discusses how the port, the city and its people have integrated and experienced conflicts through using cultural heritage. It identifies how CHPC has been defined, preserved, managed and repurposed from 1980 to 2020, and analyzes the challenges, risks (both natural and anthropogenic), trade-offs, and opportunities involved in cultural heritage management in the sustainable development of port cities. It also examines the approaches and extent of public engagement with CHPC. My research applies a mixed-method approach including semi-structured interviews, site-inspection, observation, document and policy analysis in the main case Dublin and three comparative cases Lisbon, Rotterdam and Gothenburg. QDA and GIS technologies, photographic documentation and quantitative manners are also employed to complement and testify the qualitative analysis and integrally present the visualized research outcomes. In the context of reimagination and recreation of post-industrial port cities after experienced drastic changes like increasing globalization and recessions, various and even conflicting narratives regarding repurposing CHPC have been revealed through waterfront regeneration. Such narratives further reflect the issues of identity, hyper-instrumentalization of culture and the lack of holistic perspectives on heritage management and planning. Furthermore, the comparative analysis discovers that the tradition of democracy, as well as policies and tools to facilitate participation at multiple stages of decision-making, contribute to different extents of engagement. Currently, most studies regarding heritage in waterfront regeneration focus on material elements and are from urban planning or governance angles, while the viewpoints from heritage management and historical perspectives are limited. My research fills this gap and provides empirical evidence by comparing four different port-city settings. Moreover, building on existing research, it advances the state-of-the-art by providing in-depth analysis that combines interdisciplinary knowledge of cultural heritage management, environmental history, public history, natural and social marine science, cultural policy and socio-economic systems.
APPROVED
Keywords: cultural heritage; port cities; public history; environmental history; post-industrial societies